New frontier: Three painters from Shenzhen and their relation with the Hong Kong art market. (1st October 2021) - Vigneron, Frank
Drawn towards Hong Kong because of what appears to be a thriving art market, many artists from the People's Republic of China are now looking towards Shenzhen, the Special Economic Zone created nearby in the 1980s, for conducting their practices. Launched as an economic testing ground by Deng Xiaping, Shenzhen is now experiencing new and profound changes. The development of new art institutions has been the reason for the emergence of an art scene that is fostering the creation of original art practices, especially in the field of painting. This article takes as example three practitioners and explains the reasons why they have chosen to live there and how they are negotiating their position from this city within the local art ecology as well as the art market of Hong Kong. The first of these artists, Liang Quan (), has lived in Shenzhen since the 1990s and is a representative of contemporary forms of literati painting, while the other two, Zhou Li () and Xue Feng (), are more recent arrivals who are both abstract painters engaging sometimes in the creation of installations and public art projects. To better understand the position of these artists towards the demands of an art market, this article will also explain how the idea of commoditization, which was so repellent to the practitioners of institutional critique in the Euro-American context of the 1960s and 1970s, has not been experienced in Mainland China in quite the same way.